2022
DOI: 10.3390/ijerph19084647
|View full text |Cite
|
Sign up to set email alerts
|

The Childbirth Fear Questionnaire and the Wijma Delivery Expectancy Questionnaire as Screening Tools for Specific Phobia, Fear of Childbirth

Abstract: Background: Perinatal anxiety and related disorders are common (20%), distressing and impairing. Fear of childbirth (FoB) is a common type of perinatal anxiety associated with negative mental health, obstetrical, childbirth and child outcomes. Screening can facilitate treatment access for those most in need. Objectives: The purpose of this research was to evaluate the accuracy of the Childbirth Fear Questionnaire (CFQ) and the Wijma Delivery Expectations Questionnaire (W-DEQ) of FoB as screening tools for a sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 111 publications
0
1
1
Order By: Relevance
“…The results of our study showed that women in rural areas had significantly high level of prenatal FOC, which exceeded the levels found in relevant study in Canada [35] and were similar to those found in Iran [36] and Hong Kong, China [37]. Our study shows that more than half of the participants had relatively high prenatal FOC (WDEQ-A scores ≥ 66), which is higher than in some studies in Australia (26%), Portugal (28%) and Sweden (26%) [38][39][40].…”
Section: Discussioncontrasting
confidence: 92%
“…The results of our study showed that women in rural areas had significantly high level of prenatal FOC, which exceeded the levels found in relevant study in Canada [35] and were similar to those found in Iran [36] and Hong Kong, China [37]. Our study shows that more than half of the participants had relatively high prenatal FOC (WDEQ-A scores ≥ 66), which is higher than in some studies in Australia (26%), Portugal (28%) and Sweden (26%) [38][39][40].…”
Section: Discussioncontrasting
confidence: 92%
“…A large body of evidence has supported that severe fear of childbirth might increase the risk of preterm childbirth, dystocia, elective cesarean section, and emergency cesarean Sects. [6][7][8]. The expected labor pain during the latent phase could reduce the strong stress of the parturient and help the parturient to maintain her physical fitness and cooperate to complete the delivery.…”
Section: Introductionmentioning
confidence: 99%